Xylella fastidiosa subsp. Pauca strains fb7 and 9a5c from citrus display differential behavior, secretome, and plant virulence - de Souza, Jessica Brito; Almeida-Souza, Hebréia Oliveira; Zaini, Paulo Adriano; Alves, Mônica Neli [UNESP]; de Souza, Aline Gomes; Pierry, Paulo Marques; da Silva, Aline Maria; Goulart, Luiz Ricardo; Dandekar, Abhaya M.; Nascimento, Rafael (MDPI, 2020)
Xylella fastidiosa colonizes the xylem of various cultivated and native plants worldwide. Citrus production in Brazil has been seriously affected, and major commercial varieties remain susceptible to Citrus Variegated Chlorosis (CVC). Collective cellular behaviors such as biofilm formation influence virulence and insect transmission of X. fastidiosa. The reference strain 9a5c produces a robust biofilm compared to Fb7 that remains mostly planktonic, and both were isolated from symptomatic citrus trees. This work deepens our understanding of these distinct behaviors at the molecular level, by comparing the cellular and secreted proteomes of these two CVC strains. Out of 1017 identified proteins, 128 showed differential abundance between the two strains. Different protein families were represented such as proteases, hemolysin-like proteins, and lipase/esterases, among others. Here we show that the lipase/esterase LesA is among the most abundant secreted proteins of CVC strains as well, and demonstrate its functionality by complementary activity assays. More severe symptoms were observed in Nicotiana tabacum inoculated with strain Fb7 compared to 9a5c. Our results support that systemic symptom development can be accelerated by strains that invest less in biofilm formation and more in plant colonization. This has potential application in modulating the bacterial-plant interaction and reducing disease severity.
Keywords: Hemolysin-like protein; LC-MS/MS; Lipase; Pathogenicity; Peptidase; Phytopathogen; Plant-pathogen interaction; Secretome